Prognostic impact of preoperatively elevated and postoperatively normalized carcinoembryonic antigen levels following curative resection of stage I‐III rectal cancer. (4th December 2019) - Nakamura, Yuya; Shida, Dai; Tanabe, Taro; Takamizawa, Yasuyuki; Imaizumi, Jun; Ahiko, Yuka; Sakamoto, Ryohei; Moritani, Konosuke; Tsukamoto, Shunsuke; Kanemitsu, Yukihide
Abstract: Background: Preoperative and early postoperative serum carcinoembryonic antigen (CEA) levels are known prognostic factors in rectal cancer. Recently, a large‐scale study on colon cancer revealed that "preoperatively elevated and postoperatively normalized CEA levels" is not an indicator of poor prognosis. However, whether this hold true in rectal cancer patients is unknown. This study aimed to investigate the prognostic significance of preoperatively elevated and postoperatively normalized CEA levels in rectal cancer patients undergoing curative resection. Methods: Subjects were consecutive stage I‐III rectal cancer patients who underwent curative resection without preoperative treatment at National Cancer Center Hospital between 2000 and 2015. Overall survival (OS) and the hazard function of recurrence or death were analyzed according to the CEA levels, as follows: normal preoperative CEA (normal group), preoperatively elevated but postoperatively normalized CEA (normalized group), and preoperatively and postoperatively elevated CEA (elevated group). Results: The normalized group (n =235) had worse OS (HR 1.49, 95% CI 1.08‐2.04; P  = .0142) compared to the normal group (n = 1208), and better OS compared to the elevated group (n = 47) (HR 0.53, 95% CI 0.31‐0.91; P  = .0208). The elevated group had the highest and earliest peak in hazard function, followed by the normalized group and the normal group, with median times to recurrence of 8.8, 15.5, and 18.5 months, respectively ( P  = .0223). Conclusions: Prognosis after resection of rectal cancer was worse in patients with preoperatively elevated and postoperatively normalized CEA compared to those with normal preoperative CEA. Patients with elevated preoperative CEA might require intensive follow‐up even if levels normalize after resection, especially in earlier periods, for early detection of recurrence. Abstract : Recently, a large‐scale study on colon cancer revealed that "preoperatively elevated and postoperatively normalized CEA levels" is not an indicator of poor prognosis. In this study, we demonstrated that, in rectal cancer, "preoperatively elevated and postoperatively normalized CEA levels" is a definitive indicator of poor prognosis.